The Effect of Cover Crops on Soil Quality in Gogo Rice Planting in an Effort to Increase Yield - M. Iqbal Atmayadi Saifuddin; Taufik Fauzi; A.A.K. Sudharmawan (Jurnal Biologi Tropis, 2023)
Organic matter is one of the important factors that can determine the level of soil fertility and health. The presence of organic matter in the soil is currently quite worrying. This is due to the behavior of the farmers themselves who tend to carry out inappropriate cultivation and the excessive use of inorganic fertilizers and the use of chemical pesticides that exceed the dosage. It is necessary to take appropriate measures so that the organic matter in the soil is not reduced. The analysis was carried out descriptively by conducting a literature study on relevant literature and conducting a qualitative analysis. Based on the results of a review of international and national journals that cover crops can play an active role in the growth rate and yield of cultivated plants. Ground cover plants can be used as conservation plants, soil health and fertility and the environment as erosion control, maintaining soil moisture, controlling pest populations, suppressing weed growth. The advice that can be given from this paper is the need for further research on the use of cover crops as a source of organic matter in soil balance and agro-ecosystems.